PENGOLAHAN LIMBAH PADAT ORGANIK MENJADI KOMPOS MELALUI PROGRAM ZERO WASTE PADA PERKEBUNAN NANAS DI PROVINSI LAMPUNG: PENGOLAHAN LIMBAH PADAT ORGANIK MENJADI KOMPOS MELALUI PROGRAM ZERO WASTE PADA PERKEBUNAN NANAS DI PROVINSI LAMPUNG - Muhammad Aqsol Bayhaqy; Hardoyo, Hardoyo; Natalina, Natalina (Fakultas Teknik Universitas Hamzanwadi, 2025)
Rapid industrial development has contributed to an increase in the volume of waste produced, including organic solid waste. One of a pineapple plantation and agro-industrial company in Lampung Province has implemented a zero waste program to address the problem of organic solid waste arising from the pineapple production process. This fieldwork aims to examine the process of converting organic solid waste into compost through a zero waste approach, as well as to identify the technical and operational obstacles encountered in its implementation. Waste processing uses aerobic composting and vermicomposting methods. The processing results in three types of compost, namely bulky, premium, and pellet, which are reused as fertilizer on plantation land. The zero waste program that is implemented not only contributes to environmental preservation but also provides economic added value for the company.